2010
DOI: 10.1371/journal.pone.0013699
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Activity of 2-Deoxy-D-Glucose

Abstract: BackgroundDuring tumor angiogenesis, endothelial cells (ECs) are engaged in a number of energy consuming biological processes, such as proliferation, migration, and capillary formation. Since glucose uptake and metabolism are increased to meet this energy need, the effects of the glycolytic inhibitor 2-deoxy-D-glucose (2-DG) on in vitro and in vivo angiogenesis were investigated.Methodology/Principal FindingsIn cell culture, 2-DG inhibited EC growth, induced cytotoxicity, blocked migration, and inhibited activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 49 publications
7
94
0
4
Order By: Relevance
“…3 E and F), suggesting that the use of 2DG in vivo does not impair T-cell functions. Also, a recent study suggested that, under normoxic conditions, the primary activity of 2DG might not be to inhibit glycolysis but rather to interfere with N-linked glycosylation, leading to ER stress (4,28). It is of course important to keep in mind that escape from the immune-mediated surveillance of dying cells is among the characteristics of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…3 E and F), suggesting that the use of 2DG in vivo does not impair T-cell functions. Also, a recent study suggested that, under normoxic conditions, the primary activity of 2DG might not be to inhibit glycolysis but rather to interfere with N-linked glycosylation, leading to ER stress (4,28). It is of course important to keep in mind that escape from the immune-mediated surveillance of dying cells is among the characteristics of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the N-terminal peptide in inhibiting angiogenesis was tested in the in vivo murine Matrigel plug assay, as previously described (Auerbach et al, 2003;Merchan et al, 2010). Mice were injected with Matrigel in the presence of PBS alone (negative control) or Matrigel mixed with VEGF and basic FGF (bFGF; positive control).…”
Section: Anxa2 N-terminal Competitive Peptide Inhibits Angiogenesis Imentioning
confidence: 99%
“…The Matrigel plug assay was performed as described previously (Merchan et al, 2010). Briefly, 500 l of unpolymerized Matrigel (BD Biosciences) (~20 mg/ml), either alone (negative control), mixed with bFGF and VEGF (100 ng/ml each), or in the presence of 5 M of the LGKLSL or LCKLSL peptides in combination with bFGF and VEGF (treatment group), was injected subcutaneously at the left lower abdominal wall of four groups of athymic nude mice (4-to 6-weeks-old) (Harlan, Madison, WI).…”
Section: In Vivo Angiogenesis (Matrigel Plug) Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In these cells, flux of glucose through the pentose phosphate shunt is required for efficient generation of NADPH, which maintains the high ratio of reduced to oxidized glutathione (GSH/GSSG) required for optimal control of oxidative stress; in addition, glycolytic flux generates pyruvate, which can function as a peroxide scavenger [9]. The increased glucose uptake in cancer cells is most probably a requirement to meet multiple processes including antioxidant defenses, protein glycosylation and angiogenesis [10,11]. It has been suggested that many cancers may be selectively susceptible to oxidative damage if systemic glucose deprivation is imposed.…”
Section: Introductionmentioning
confidence: 99%